STUDI EKSPERIMEN KUAT TEKAN BETON NON AGREGAT KASAR SEMEN PCC DENGAN SIKAMENT LN - Siregar, Derina Ika Kumalasari; Mungok, Chrisna Djaya; Samsurizal, Eddy (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2014)
This paperpresents the results ofthe use ofthe added materialismixed into theSikamentLN mortarbymixingvaryinglevels of0.6%, 1%, 1.5%. Specimensmade​​cuboidwith a length of5cm, width5cmand height5cm. Aimstodetermine how much influencethe addition ofvariantsSikamentLN0.6%, 1%, and1.5% in thecompressive strengthof mortarbasedfunctionsthat usecementPCCage. job mix formula refers to the ratio of cement to fine aggregate (sand) is a standard ASTM C 109 / 109m - 02